Readiness to Implement PSAK 112 at Yayasan Wakaf Bangun Nurani Bangsa - Nabila Fairuz Fatin; Krisno Septyan; Ayunita Ajengtiyas Saputri Mashuri (Journal of Islamic Economics Lariba, 2019)
This research aims to know the readiness of implementation of PSAK 112 on Bangun Nurani Bangsa Waqf Foundation. The methods used in this research is qualitative method and also with phenomenology approach and paradigm interpretive. The research result show that the Bangun Nurani Bangsa Waqf Foundation is not ready to implement PSAK 112. Bangun Nurani Bangsa Waqf Foundation needs to make adjustments to some components of the financial statements. However, the constraints of lack of human resources and the lack of human resources for the financial sector need to be addressed by Bangun Nurani Bangsa Waqf Foundation.